1986
DOI: 10.1055/s-2007-1001868
|View full text |Cite
|
Sign up to set email alerts
|

Atraumatische Diagnostik und semi-invasive Therapie des Subklaviaanzapfsyndroms mit Hilfe der perkutanen transluminalen Angioplastie (PTA). Ein zeitgemäßes Konzept

Abstract: Percutaneous transluminal angioplasty (PTA) is a semiinvasive, non-operative transvascular technique for dilatation of stenosed vessel segments by help of balloon catheters. This technique was applied to 30 out of 42 patients with a subclavian steal mechanism due to highgrade proximal subclavian artery (PSA) lesions. The transfemoral, transaxillary or both approaches were used. A staging of the severity of the subclavian steal mechanism on the basis of the pre-interventional Doppler ultrasound findings (Grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…RINGELSTEIN et al (16) used continuous wave (CW) Doppler findings for the selection of patients for angioplasty. WINTER et al (21) found that the complete subclavian steal syndrome with a constant reversal of vertebral artery flow was reliably detected (1 6 cases), and in an incomplete steal syndrome (5 cases) CW sonography proved superior to angiography.…”
Section: Discussionmentioning
confidence: 99%
“…RINGELSTEIN et al (16) used continuous wave (CW) Doppler findings for the selection of patients for angioplasty. WINTER et al (21) found that the complete subclavian steal syndrome with a constant reversal of vertebral artery flow was reliably detected (1 6 cases), and in an incomplete steal syndrome (5 cases) CW sonography proved superior to angiography.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, 31 small series dealing with total occlusion of the aortic arch vessels have been published, with a technical success rate of 67.5% (range 0–100%) (table 3) [6, 7, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37]. However, this rate would be higher if only cases treated with stenting-PTA were considered.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism serves as a protection against cerebral embolism during subclavian PTA [10]. In cases of lowgrade proximal subclavian stenoses without a typical steal phenomenon, PTA is not recommended [11].…”
Section: Discussionmentioning
confidence: 99%